How to Best Measure and Characterize Symptoms of Patients with Pelvic Floor Disorders - Savulionyte, Goda; Bordeianou, Liliana (Clinics in Colon and Rectal Surgery, 2025)
Pelvic floor disorders (PFDs) are common and can be associated with various symptoms, including fecal incontinence, constipation, urinary incontinence, lower urinary tract symptoms, sexual dysfunction, and pelvic pain. Characterizing symptoms can be challenging due to limitations in patient reporting, provider ability to collect data, and the instruments used to collect the data. Symptoms are assessed using patient-reported outcome measures (PROMs), instruments that can be generic or disease-specific. Here, we describe the frequently used and recommended instruments for assessing symptoms of PFDs. We review the Pelvic Floor Disorders Consortium (PFCD) consensus document called IMPACT (Initial Measurement of Patient-reported Pelvic Floor Complaints Tool), a collection of recommended instruments in their unaltered form as well as within a consolidated short form. A multidisciplinary approach to patient care and interpretation of data is important to best characterize symptoms of PFDs. Future steps should include further collaborating across specialties and with patients to develop more condition-specific and patient-centered PROMs.
Keywords: pelvic floor; patient-reported outcomes; colorectal; genitourinary